Perpetual creation - Javadi Amouli (حکمت اسرا, 2014)
In Commentary of changeable existence with the various foundations, there have been different expressions such as Generation and Corruption, Motion, Natural Occurrence and Perpetual Creation. In this research, the differences between perpetual creation and other meanings which is said about changeable existence is mentioned. And inconformity of perpetual creation with perpetual accident of Ash'arities which is erroneous expression, and also, substantial motion which is obvious and correct is have been explained. Finally, Existence of rational or revealed arguments for perpetual creation is rejected and for this objection is declaring that in perpetual creation «unity or priority and follower things can't be retained» and it indicates that this unity which Joundi cites it through Efficient and breath of the All-merciful in Fas-e-Soleimani description is not providable.